Implementation of Decentralized Water Resources Management Based on Integrated Water Resources Management in Indonesia (A Case Study of Cisadane River Basin) - Djamres, Eilif Kurnia Deda; Suhadak, Suhadak; Wike, Wike (Jurnal Ilmiah Administrasi Publik, 2018)
Since the last two decades, Indonesia has been performed decentralization for managing water resources. However, some problems related to water management still exist such as flood, drought, and ego sectoral among stakeholders. Cisadane river basin was used as a study area due to this river basin is one of the national strategic river basin and faced the fastest growing population and land conversion function in Indonesia. Using Grindle model (1980), we analyzed the performance of the policy and figure out its supporting and constraining factors. As a result, in general, implementation of decentralized water resources management based on â€œIntegrated Water Resource Management (IWRM)â€ principles at Cisadane river basin has been running well. Nevertheless, some problems related communication among stakeholders, public participation, and limited resources are the main issues of decentralized water resources management in Indonesia and can hamper the policy to reach its goals.